Faith and Social Capital After the Debt Crisis - Dinham, A. author. aut Link
XIV, 204 p.
Keywords: This book explores what becomes of faiths when seen as social capital. In the grip of the current debt crisis, where the social and capital seem increasingly unbalanced, this book examines whether faiths can help rebalance society through drawing communities together.